The Knowledge Level of Female University Students about Human Papillomavirus - Taylor, Joy Annabelle (East Carolina University, 2017)
Awareness and knowledge of Human Papillomavirus (HPV) remains a serious health issue, and an area for continued research. In this study, a survey of female undergraduates at ECU found that while respondents were aware of HPV, there were troubling deficits in their knowledge of it. Vaccination against HPV was not widespread among the respondents. These findings suggest the continued need to educate young women about the risks of HPV. In a 2001 report, the Population Reference Bureau branded the human papillomavirus as a “hidden epidemic” (PRB, 2001). The virus, commonly known as HPV, is the most common sexually transmitted infection. Although the body’s immune system can combat HPV in many cases, there are many other cases of virus causing in genital warts and various cancers (CDC, 2015). That includes cervical cancer in women. The overarching goal of this study was to take an updated look at the levels of HPV awareness and knowledge among college females. The role of educational attainment in awareness and knowledge is of specific interest, particularly given the link between HPV and cervical cancer. Data was gathered through a Web-based survey distributed to female undergraduates at East Carolina University, a southeastern public university. The survey instrument adopted awareness and knowledge questions from the literature, and it collected demographic variables such as age and race/ethnicity. This study asked the following research questions: Research Question 1: What is the level of awareness of HPV among college females? Research Question 2: What is their knowledge level about it? Research Question 3: What percentage of college females been vaccinated against HPV?
Keywords: HPV; knowledge; health